Perkembangan Wisata Kuliner Kalimantan Tengah Pasca Pandemi Covid-19 (Studi Kasus Pada Taman Tunggal Sangomang) - Suswanto Suswanto; Fransiska Inge Angelina (Pringgitan, 2022)
Tourism development in a region brought benefits to community either economically, social, and culture. Palangka Raya has various tourism objects. One of them is Taman Kuliner Tunggal Sangomang, but since the COVID-19 pandemic that swept across much of the world affected different sectors including the culinary sector. It needs correct strategy to pull tourists interest to visit especially in a state of COVID-19 pandemic. This research is descriptive qualitative which review Taman Kuliner Tunggal Sangomang tourism potential development strategy based on internal and external factors. Population in this research are visitors at Taman Kuliner Tunggal Sangomang by using SWOT analysis. Research shows that by reviewing internal and external factors,will get a development strategy which can be applied to Taman Kuliner Tunggal Sangomang in a state of COVID-19 pandemic.Keywords: Development Strategy, COVID-19 Pandemic, SWOT Analysis